Leveraging Integrated Student Support to Identify and Address COVID-19-Related Needs for Students, Families, and Teachers - Courtney Pollack; Maria Theodorakakis; Mary E. Walsh (SAGE Publishing, 2021)
As COVID-19 shuttered schools, it created widespread student and family needs and exacerbated challenges stemming from long-standing racial and economic inequities. Here, we examine how an evidenced-based, integrated student support intervention responded to systematically identify and address the academic and nonacademic needs of students and families in 94 high-poverty, urban schools. We conduct thematic analysis of open-ended survey responses about intervention personnel's work in spring 2020 and triangulate findings with descriptive analyses of service provision records and mid-spring estimates of crucial needs. We find that intervention schools developed specific processes to respond to immediate needs, which included resource, academic, and socioemotional support. To accomplish this, the intervention leveraged existing processes and relationships to maintain intervention-specific practices, facilitate referrals and connections to resources, and expand direct intervention for education stakeholders. Findings elucidate practices for meeting academic and nonacademic needs that affect student learning and that may arise in future schooling disruptions.